2018
DOI: 10.24071/llt.2018.210212
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Writing skill is considered a difficult skill for some of the students because of limited vocabulary as well as grammatical weaknesses. Therefore, this study aims to investigate further the practice of GT in EFL essay writing as wells as its role in language learning. The study was conducted in Universitas Kristen Krida Wacana, involving eight respondents from Ukrida Department of English. Two methods were used, such as mediated-observation and interview. A writing task was given to each respondent and her/his… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(33 citation statements)
references
References 4 publications
11
22
0
Order By: Relevance
“…Electronic translation may occur with the intervention of human beings or without it (Akbari, 2014). By and large, the majority of EFL students use "MT as a dictionary (specifically MT is easier than a dictionary)" (Clifford et al, 2013, p. 112) to translate lexical items or check up their meaning in vocabulary learning activities (Chandra & Yuyun, 2018;Clifford et al, 2013). Using MT as a translation tool applies to diverse language combinations, including English/Arabic.…”
Section: Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations
“…Electronic translation may occur with the intervention of human beings or without it (Akbari, 2014). By and large, the majority of EFL students use "MT as a dictionary (specifically MT is easier than a dictionary)" (Clifford et al, 2013, p. 112) to translate lexical items or check up their meaning in vocabulary learning activities (Chandra & Yuyun, 2018;Clifford et al, 2013). Using MT as a translation tool applies to diverse language combinations, including English/Arabic.…”
Section: Literature Reviewmentioning
confidence: 99%
“…AlQahtani (2015) pointed out that L2 readers face formidable challenges unless they have rich knowledge about vocabulary and their use in context. Empirically, learning vocabulary plays a vital role in the reading skill and all other language skills because it is sentential to the successful uses of language (Chandra & Yuyun, 2018). Research has revealed that L2 learners achieve more when they have rich knowledge about vocabulary in quantity and quality (AlQahtani, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…According to Nomass (2013), integrating the role of technology with that of the instructor is an optimal way to achieve "advanced learning results" (p. 111). Some EFL instructors are not speakers of the target language, so they cannot rely on MT to verify their students' correct understanding of the actual meaning of vocabulary in context (Chandra & Yuyun, 2018), but still, there are several strategies that EFL instructors can adopt in order to complement the role of the translation software in the learners' acquisition of new vocabulary. If used in a pedagogicallysound manner, these strategies can develop students' skills to use MT effectively and independently in advanced phases without the guidance of their teachers.…”
mentioning
confidence: 99%